Hubungan Minat Belajar terhadap Prestasi Belajar Fisika - Leo Charli; Tri Ariani; Lusi Asmara (SPEJ (Science and Physic Education Journal), 2019)
The purpose of this study was to find out the relationship between learning interest in learning achievement in physics of class XI students at Karang Jaya Public High School 2017/2018 Academic Year. The research method used is correlation research. The population is all class students of Karang Jaya High School 2017/2018 Academic Year totaling 103 people and as a sample 1 class is taken, namely the XIA class totaling 26 people. Data collection techniques were carried out by questionnaire technique. The magnitude of the correlation between the two variables tested (rxy) is 0.50 (medium correlation coefficient). The regression equation is Y = 42 + 0.51X. the value of b which is positive, means that interest in learning has a positive effect on student learning achievement. The results of the calculation of linearity test Fcount = 8.11 while from the F distribution table at the significance level α = 0.05 where db re g (b 1a) 1 and db res = 26 this means there is a linear relationship of learning interest with student achievement in physics learning. The results of this study indicate that there is a significant relationship between interest in learning with physics learning achievement of students of Class XI Karang Jaya Public High School 2017/2018 Academic Year. It is expected that students always train themselves to dare to appear in expressing their opinions in public places. Keywords: interest, learning achievement